Place-Based Diminished Returns of Parental Educational Attainment on School Performance of Non-Hispanic White Youth - Assari, Shervin; Boyce, Shanika; Bazargan, Mohsen; Caldwell, Cleopatra H.; Zimmerman, Marc A. (Frontiers in Education, 2020)
Background Youth educational outcomes are a function of a wide range of factors including parental education level. This effect, however, is shown to be smaller for African American, Hispanic, and Asian American youth, a pattern called Marginalization-related Diminished Returns (MDRs). It is, however, unknown if it is race/ethnicity or other conditions associated with race/ethnicity (e.g., poor neighborhood quality) which reduces the marginal returns of parental education for youth. Aim To explore whether MDRs are only due to race/ethnicity or if they also remain for non-Hispanic Whites in poor neighborhoods, we compared the association between parental education level and adolescents’ school performance based on neighborhood quality in a nationally representative sample of non-Hispanic Whites in the United States. Methods This cross-sectional study used wave 1 of the Add Health study, an ongoing nationally representative cohort, 1994–2019. Participants included 849 non-Hispanic White adolescents between the ages of 12 and 21 years and their parents. The independent variable was parental education level, which was treated as a continuous measure. Age, grade, gender, and parental marital status were the covariates. The dependent variable was school performance (sum of school grades in Math, English, History, and Science). Linear regression models were used for data analysis. Results Overall, worse neighborhood quality was associated with worse school performance. Parental education level, however, was not directly associated with youth school performance. We found a statistically significant interaction between parental education level and neighborhood quality suggesting that the strength of the association between parental education and youth school performance weakens as neighborhood quality declines. Conclusion Parental education level is a more salient determinant of youth educational outcomes in better neighborhoods. The result suggests that MDRs may not be solely due to race/ethnicity but contextual factors that commonly covary with marginalization and poverty. These contextual factors may include segregation, concentration of poverty, and social and physical neighborhood disorder.